International Spillover of Labor Market Reforms - Dao, Mai (IMF Working Papers; Working Paper ;, 2008)
This paper uses a dynamic economy model, with unionized labor markets, to analyze the effects of labor market reforms, similar to those recently introduced in Germany, on the domestic and trading partner economies. The model is calibrated on Germany and the rest of the Euro area. The results indicate that German labor market reforms have positive spillover effects on the rest of the Euro area, which operate through the channel of trade, relative price adjustment, and financial market integration. Compared to a competitive labor market, setting, unionization dampens the positive response of the domestic economy and magnifies the spillover effects.